EVALUATION OF THE EFFECTIVENESS OF COOPERATIVE LEARNING METHODS IN ENHANCING ENGLISH WRITING SKILLS AMONG ELEMENTARY SCHOOL STUDENTS - Sri Hardianty; Ach Munawi Husein; Muhammad Ishom; Era Purike; Husna Imro'athush Sholihah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This research evaluates cooperative learning methods for enhancing English writing skills in elementary school students. Emphasizing the importance of English proficiency in the globalized era, the study draws on Ministry of Education and Culture data, highlighting the widespread integration of English curriculum in Indonesian elementary schools. The research addresses the imperative of fostering writing skills, prompted by a national survey revealing that over 80% of elementary students in Indonesia struggle with expressing ideas in writing. Through an extensive literature review, the study explores the rationale, benefits, and challenges of cooperative learning in the elementary English language context. The methodology combines quantitative and qualitative elements, encompassing research design, population, sampling methods, and instruments to evaluate cooperative learning methods comprehensively. Critical examination of previous research findings informs the study's objectives, with the discussion section interpreting research findings and offering strategic recommendations for cooperative learning implementation. Considering the broader educational context, the discussion underscores the need for continuous professional development to optimize outcomes. In conclusion, the research provides valuable insights into the efficacy of cooperative learning in enhancing English writing skills at the elementary level, targeting educators, policymakers, and researchers invested in elevating English language instruction quality in elementary schools.